The Effect of PROPER Level Disclosure and C02 Emissions Intensity on Financial Distress - Sembiring, Etti Ernita; Irawan, Arry; Kusumastuti, Endah Dwi (Indonesian Journal of Economics and Management, 2023)
This study aims to examine the effect of PROPER disclosure and CO2 intensity disclosure on financial distress. This study uses secondary data with documentation data collection techniques. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2017-2021 and submitting their annual financial reports. The reason why this study uses the type of manufacturing company is because manufacturing companies are the largest companies listed on the Indonesia Stock Exchange, besides that manufacturing companies are one of the types of companies that contribute the most carbon emissions in Indonesia. This study uses the Common Effect Model (CEM). The results showed that PROPER disclosure and CO2 intensity disclosure did not significantly affect financial distress.